Improving the Beginning Reading Ability of Class I Students at State Elementary School 35 Barru Using Letter Card Media - Tarman, Tarman; Arif, A; Putri, Nursupiani; Azizah, Iffah (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to improve the early reading skills of first-grade students at SD Negeri 35 Barru using letter card media through a Classroom Action Research (CAR) approach. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Letter card media was utilized to introduce letters, pronounce letter sounds, and construct simple words interactively. The results showed a significant improvement in students' reading abilities. In the first cycle, only 59% of students met the Minimum Competency Criteria (MCC). Challenges such as difficulty recognizing letters and low student motivation were addressed in the second cycle by incorporating interactive activities like word games and paired reading exercises. By the end of the second cycle, 88% of students achieved the MCC.This study concludes that the use of letter card media is effective in enhancing students' early reading skills. The media not only aids students in recognizing letters and reading words but also increases their motivation and participation in the learning process.